Phosphorus Use Efficiency for Cucumber (Cucumis Satnus L.) Grown on Acid Soils - Hilman, Yusdar (2003)
Phosphorus (P) use efficiency for cucumber grown on acid soils was studied. The objectives of this experiment were: (i) to screen the solubility of three phosphate rocks in acid soils with the aim of selecting one phosphate rock (PR) with the best P and calcium (Ca) solubility in acid soils - a laboratory study, (ii) to determine the most economical P source, critical P level, and the relationship between P uptake (Ps) and phosphorus dissolution from PR (PDP) or Pb/P - green house study, and (iii) to improve upon P availability in an acid soil cultivated with cucumber influenced by mycorrhiza (VAM) inoculation, organic matter (OM) amendment and P rate - field study. Results of the experiment indicated that in a closed incubation system, dissolution of Indonesian phosphate rock (IPR) (30.20 to 100.00%) was the highest followed by Gafsa phosphate rock (GPR) (17.00 to 68.80%) and then China phosphate rock (CPR) (19.80 to 53.80%). Three major factors which may affect the PR dissolution were identified: (i) soil texture (STF), (ii) soil acidity (SAF) and (iii) fertilizer (FF). Soil texture (clay, silt and sand contents) and P retention capacity showed the highest magnitude (54%) of the factor effect on P dissolution. In a green house, there was significant difference between soils and P levels with regards to total plant dry matter yield (DMY), leaf area, soil N, K and Ca nutrients, and N, K and Ca uptake by cucumber at three harvests extending from 14 to 42 days. The IPR (RAE = 177.10%) and GPR (RAE = 145.50%) were superior to triple superphosphate (TSP). On the soils with high P retention capacity (> 50%), the supply of P from both IPR and GPR on cucumber were much cost effective than TSP, with relative economic effectiveness (REE) values of 495.50% and 318.60% for IPR and GPR, respectively. For GPR, there was a positive correlation between P uptake (L\Ps) and P dissolution (L\P) as well as P uptake (L\Ps), and P availability (L\Pb). Similar observation was made for IPR and not TSP. There was a close relationship between residual P determined by Pb method and P uptake (Ps) by cucumber at 28 and 42 days with correlation coefficients varying from 0.76 to 0.97 for GPR, IPR and TSP in the three acid soils.